Partial penectomy or total penectomy for T1 and T2 squamous cell carcinoma of the penis? - Zheng, Qi-Le; Wu, Yu-Peng; Zhang, Zi-Ping; Xu, Ning (Translational Cancer Research, 2019)
Background: To assess prognostic factors and survival outcomes for partial penectomy (PP) and total penectomy (TP) patients with T1 and T2 squamous cell carcinoma of the penis. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was used to identify 708 penile cancer patients. Among these, 607 underwent PP and 101 underwent TP. Kaplan-Meier analysis was used to compare survival outcomes between PP and TP patients. Univariate and multivariate Cox proportional hazards regression models were used to determine prognostic factors. Results: There were significant differences in marital status and regional lymph node removal between patients of the PP and TP groups. Multivariate regression analysis demonstrated that age [odds ratio (OR) =1.045; 95% confidence interval (CI): 1.034–1.057; P